Shear behavior of concrete beams reinforced exclusively with longitudinal glass fiber reinforced polymer bars: Experimental research - Kaszubska, Monika (2018)
This paper aims to investigate the shear failure mechanisms in beams exclusively reinforced with longitudinal glass fiber reinforced polymer bars and to propose a design-based approach to predict the shear capacity of this type of beams. An experimental program composed of seven T cross section shaped concrete beams was executed to analyze the influence of the flexural reinforcement configuration on the shear capacity and deformability of the beams. Three values of the flexural reinforcement ratio ((l)), 1%, 1.4%, and 1.80% were adopted. Digital image correlation technique was used to better capture and analyze the cracking process up to the formation of the shear failure crack. Test results indicated that the shear capacity was not dependent of (l) up to a limit of around 1.4%, but a tendency of the shear capacity to increase with (l) was registered above this limit due to a more pronounced favorable contribution of aggregate interlock and dowel effect.